TBC Bacteria Detection in Microscopic Image With Watershed Countur Method - Dawwas, Rodan Hilmi (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2023)
Tuberculosis (TB) is an infectious disease that can be detected using a sputum sample. TB cases in Indonesia have spread throughout the region; the highest cases are in West Java. This problem makes the government do some handling and prevention of TB disease. The Bandung City Health Office (DKKB) conducted a cross-test to diagnose TB using a sputum sample. So in this study, a TB bacteria detection system, namely Mycobacterium Tuberculosis (MTB), will be made in sputum samples and their number to diagnose TB. Detection and calculation of the number of MTB are done by processing the image on the sputum sample using the watershed contour detection method. In this study, sputum sample data were obtained from DKKB. The acquisition of microscopic images at each point of the field of view is carried out using an SLR camera connected directly to the microscope to replace the function of the ocular lens. In this study, the microscopic sputum sample images were classified into positive and negative using the watershed and colorspace methods and were tested on a total of 90 microscopic images. From the system testing results, the system accuracy level is 100%, and the system precision is 100% for the detection of TB diagnosis. The system processing time averaged 5.811 seconds for 90 images used.